Audit of risk-management methods in respect of their acceptance of analysis medical activity - Biryukov, V. S. (Journal of Education, Health and Sport, 2017)
The work is devoted to the analysis of accessibility, usefulness and the possibilities of introducing a number of risk management methods into medical institutions on the basis of the choice of heads medical institutions, after getting to know them with the main methods, proposed by the ISO 31000: 2009 standard. The conducted research has shown advantages of methods of "brainstorming" and the analysis of cause-effect relations by heads of medical institutions.